PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA PUZZLE TERHADAP HASIL BELAJAR PPKN SISWA KELAS V SEKOLAH DASAR - Fadillah dila; Munjiatun; Zufriady (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This research is motivated by the low learning outcomes of PPKn students of grade V of SD Negeri 184 Pekanbaru who have not met the criteria for achieving learning objectives (KKTP). It is known that low learning outcomes are caused by less varied learning in the use of learning models and media so that it reduces student activity and has an impact on student learning outcomes. This study aims to determine and describe the effect of the Problem Based Learning learning model assisted by Puzzle media on students' PPKn learning outcomes. This type of research is quantitative research with an experimental method with a One Group Pretest-Posttest Design. The sample of this study was 28 students of grade V. The data collection technique used a test with a question instrument in the form of multiple choice questions that had been tested for validity, reliability, level of difficulty and question discrimination. Based on the results of the study, the average pretest score was 57.57 and the average posttest score was 83.00, which showed an increase. The results of the hypothesis test using the Paired Sample T Test obtained a significance value (2-tailed) of 0.000 <0.05 so that Ha was accepted and H0 was rejected. The N-gain test results obtained a gain score of 0.6103, which is considered moderate, and a gain percentage of 61.03%, which is considered quite effective.